Cost‐effectiveness of classroom‐based cognitive behaviour therapy in reducing symptoms of depression in adolescents: a trial‐based analysis. (12th May 2014) - Anderson, Rob; Ukoumunne, Obioha C.; Sayal, Kapil; Phillips, Rhiannon; Taylor, John A.; Spears, Melissa; Araya, Ricardo; Lewis, Glyn; Millings, Abigail; Montgomery, Alan A.; Stallard, Paul
<x xml:space="preserve">Abstract</x> Background A substantial minority of adolescents suffer from depression and it is associated with increased risk of suicide, social and educational impairment, and mental health problems in adulthood. A recently conducted randomized controlled trial in England evaluated the effectiveness of a manualized universally delivered age‐appropriate CBT programme in school classrooms. The cost‐effectiveness of the programme for preventing low mood and depression for all participants from a health and social care sector perspective needs to be determined. Methods A trial‐based cost‐effectiveness analysis based on a cluster‐randomized controlled trial (trial registration – ISRCTN 19083628) comparing classroom‐based CBT with usual school provision of Personal Social and Health Education. Per‐student cost of intervention was estimated from programme records. The study was undertaken in eight mixed‐sex UK secondary schools, and included 3, 357 school children aged 12 to 16 years (in the two trial arms evaluated in the cost‐effectiveness analysis). The main outcome measures were individual self‐reported data on care costs, Quality‐Adjusted Life‐Years (QALYs, based on the EQ‐5D health‐related quality‐of‐life instrument) and symptoms of depression (Short Mood and Feelings Questionnaire) at baseline, 6 and 12 months. Results Although there was lower quality‐adjusted life‐years over 12 months (−.05 QALYs per person, 95% confidence interval −.09 to −.005, p = .03) with CBT, this is a 'clinically' negligible difference, which was not found in the complete case analyses. There was little evidence of any between‐arm differences in SMFQ scores (0.19, 95% CI −0.57 to 0.95, p = .62), or costs (£142, 95% CI −£132 to £415, p = .31) per person for CBT versus usual school provision. Conclusions Our analysis suggests that the universal provision of classroom‐based CBT is unlikely to be either more effective or less costly than usual school provision.